The Effect of Service Quality for Motor Vehicle Taxes (PKB) on Taxpayer Satisfaction at the Department of Revenue Service (Dispen) of Banten Province - Tatang Suhidayat (Budapest International Research and Critics University, 2021)
The background of the title determination above, that currently still very unfortunate about the relationship between the ficus (Tax Officer from Dispen Banten Province) and the motor vehicle taxpayer has not been the desired harmony. So that compliance and awareness of citizens to meet the obligation to pay Motor Vehicle Taxes well before the maturity of STNK is still far from the expected plan. This is where a dialogue with motor vehicle taxpayers is needed both formally and informally, to find out the difficulties faced by taxpayers and offer what can be helped by the Tax Office. The demands of good service will provide a sense of healthy communication between government employees who are in charge of providing services to the community, with taxpayers. This research aims to find out the Quality of Motor Vehicle Tax (PKB) services provided by the Revenue Office (Dispen) of Banten Province, to find out the Level of Satisfaction of Taxpayers in the Revenue Office (Dispen) of Banten Province, to find out how much influence the quality of Motor Vehicle Tax (PKB) services on taxpayer satisfaction in the Revenue Office (Dispen) of Banten Province. The method used in this study is a survey research method with a quantitative verification approach. Then the result of the test t resulted in that t table is smaller i.e. t count 9.7034 while t table 1.661 or (t count 9.7034 > t table 1.661).